Preparation and properties of antibacterial styrene‐acrylic emulsion based on bis‐quaternary ammonium salt‐containing mono‐methacrylates as polymerizable antibacterial agents. (26th December 2021) - Zhou, Xiaopei; He, Jingwei; Xiong, Shaobo; Zhou, Furong; Xiang, Hui; Liu, Fang
Abstract: With the aim to prepare antibacterial styrene‐acrylic emulsion, a series of bis‐quaternary ammonium salt‐containing mono‐methacrylates MEQABr‐ x ( x  = 12, 14, 16) were synthesized as polymerizable antibacterial agents via two steps. The chemical structures of MEQABr‐ x ( x  = 12, 14, 16) were confirmed by proton nuclear magnetic resonance ( 1 H‐NMR) and Fourier transform infrared (FTIR). The Minimum inhibitory concentration (MIC), Minimum bactericidal concentration (MBC), and Critical micelle moncentration (CMC) results showed that MEQABr‐ x ( x  = 12, 14, 16) had antibacterial properties and surface properties which was influenced by its alkyl chain length. The antibacterial emulsion (SAQ x ‐ n ) was synthesized by emulsion polymerization of styrene (St), butyl acrylate (BA), acrylic acid (AA) and MEQABr‐ x ( x  = 12, 14, 16). The structures of its films (SAQ x ‐ n ‐F) were characterized by attenuated total reflectance‐FTIR. The effects of MEQABr‐14 content or alkyl chain length of MEQABr‐ x ( x  = 12, 14, 16) on emulsion and its films were investigated in the aspect of particle sizes, pencil hardness, adhesive force grade, thermal stabilities, surface morphology, particle morphology, and so forth. The films (SAQ x ‐9‐F) with 9 wt% content of MEQABr‐ x ( x  = 12, 14, 16) showed the nearly 100% antibacterial rate against Escherichia coli and Staphylococcus aureus, indicating its potential to be used as antibacterial coating.